The causal relationship between genetically determined telomere length and meningiomas risk - Yu, Weijie; Mei, Yunyun; Lu, Zhenwei; Zhou, Liwei; Jia, Fang; Chen, Sifang; Wang, Zhanxiang (Frontiers in Neurology, 2023)
Background: Studies have shown that longer leukocyte telomere length (LTL) is significantly associated with increased risk of meningioma. However, there is limited evidence concerning the causal association of LTL with benign and malignant meningiomas or with the location of benign tumors.We used three LTL datasets from different sources, designated by name and sample size as LTL-78592, LTL-9190, and LTL-472174. The linkage disequilibrium score (LDSC) was used to explore the association between LTL and meningioma. We utilized two-sample bidirectional Mendelian randomization (TSMR) to evaluate whether LTL is causally related to meningioma risk. We adjusted for confounders by conducting multivariable Mendelian randomization (MVMR).In the LTL-78592, longer LTL was significantly associated with increased risk of malignant (odds ratio (OR) = 5.14, P = 1.04×10 -5 ), benign (OR = 4.81, P < 0.05), benign cerebral (OR = 5.36, P < 0.05) and benign unspecified meningioma (OR = 8.26, P < 0.05). The same results were obtained for the LTL-9190. In the LTL-472174, longer LTL was significantly associated with increased risk of malignant (OR = 4.94, P < 0.05), benign (OR = 3.14, P < 0.05), and benign cerebral meningioma (OR = 3.59, P < 0.05). Similar results were obtained in the MVMR. In contrast, only benign cerebral meningioma displayed a possible association with longer LTL (OR = 1.01, P < 0.05). No heterogeneity or horizontal pleiotropy was detected.In brief, genetically predicted longer LTL may increase the risk of benign, malignant, and benign cerebral meningiomas, regardless of the LTL measure, in European populations.